Comparative Effectiveness of Complete Revascularization Strategies in Patients With ST-Segment Elevation Myocardial Infarction and Multivessel Disease: A Bayesian Network Meta-Analysis - Zhao, Lingyue; Guo, Wenqin; Huang, Weichao; Wang, Lili; Mo, Fanrui; Chen, Xiehui; Li, Chaoyang; Huang, Siquan (Frontiers in Cardiovascular Medicine, 2021)
Whether fractional flow reserve (FFR) should be available for revascularization in patients with ST-segment elevation myocardial infarction (STEMI) and multivessel (MVD) is controversial. We aimed to compare the efficacy of various complete revascularization (CR) regimens for STEMI patients with MVD. The PubMed, Cochrane Library databases, and clinicaltrial.gov were searched for the randomised controlled trials (RCTs) comparing the FFR-guided CR, angiography-guided CR, and culprit-only revascularization (COR) strategies in STEMI patients with MVD. A Bayesian random-effects model was employed to synthesis the evidence in network meta-analysis. We used relative risk (RR) and 95% credible interval (CrI) as measures of effect size. The primary endpoint was the composite outcome of all-cause mortality or myocardial infarction (MI). Twelve RCTs were included. Angiography-guided CR showed a lower event rate of the composite outcome (RR, 0.68; 95%CrI, 0.50–0.87), all-cause mortality (RR, 0.75; 95%CrI, 0.55–0.96), MI (RR, 0.63; 95%CrI, 0.43–0.86), and repeat revascularization (RR, 0.36; 95% CrI, 0.24–0.55) compared with COR. Additionally, angiography-guided CR had a lower risk of primary outcome (RR, 0.64; 95%CrI, 0.38–0.94) and MI (RR, 0.58; 95%CrI, 0.31–0.92) than FFR-guided CR. The difference between the FFR-guided CR and COR in terms of composite outcome, all-cause mortality, and MI was similar. Angiography-guided CR was associated with the highest probability of optimal treatment for the primary outcome (98.5%), followed by FFR-guided CR (1.2%) and COR (0.3%). STEMI patients with MVD benefitted more from angiography-guided CR than from FFR-guided CR. However, only one study comparing the effectiveness of FFR-guided and angiography-guided PCI; thus, the comparison between FFR-guided and angiography-guided PCI was mainly reply on the indirect evidence. Therefore, further studies directly comparing the effectiveness of these two CR strategies are warranted.